The influence of website characteristics on online consumer loyalty - guo, lerui (2007)
The aim of the dissertation is to investigate the relationship between website characteristics, consumer value, and the consumer loyalty in the on-line retail context. In order to understand this aim comprehensively, this investigation went through two research stages, including the focus group and survey conduct. The website characteristics encompassed website design, value proposition, customer service, and security. The study confirms that existing literature that website characteristics have positive relationship with consumer value, which affects consumer loyalty as a result. However, different elements of website characteristic result in different level of consumer value, including utilitarian and hedonic one. The findings have great implication for practitioner in the online business context.